Stationary phase reorganisation of the Escherichia coli transcription machinery by Crl protein, a fine-tuner of σ(s) activity and levels - Typas, Athanasios (Nature Publishing Group, 2007)
Upon environmental changes, bacteria reschedule gene expression by directing alternative sigma factors to core RNA polymerase (RNAP). This sigma factor switch is achieved by regulating relative amounts of alternative sigmas and by decreasing the competitiveness of the dominant housekeeping σ(70). Here we report that during stationary phase, the unorthodox Crl regulator supports a specific sigma factor, σ(S) (RpoS), in its competition with σ(70) for core RNAP by increasing the formation of σ(S)-containing RNAP holoenzyme, Eσ(S). Consistently, Crl has a global regulatory effect in stationary phase gene expression exclusively through σ(S), that is, on σ(S)-dependent genes only. Not a specific promoter motif, but σ(S) availability determines the ability of Crl to exert its function, rendering it of major importance at low σ(S) levels. By promoting the formation of Eσ(S), Crl also affects partitioning of σ(S) between RNAP core and the proteolytic σ(S)-targeting factor RssB, thereby playing a dual role in fine-tuning σ(S) proteolysis. In conclusion, Crl has a key role in reorganising the Escherichia coli transcriptional machinery and global gene expression during entry into stationary phase.